Uncovering the Circumstances of Performance Information Use Findings from an Experiment. Issue 1 (2nd January 2016) - Moynihan, Donald P.
ABSTRACT: The diffusion of quantitative measures of performance has been one of the most widespread trends in government in past decades. This trend is motivated partly by the hope that policymakers will use performance data, but we know little about the basic tendency of individuals to incorporate and use performance information. This article draws from interactive dialogue theory to argue that the connection between data and decisions will not be automatic, but will depend upon circumstances, such as the nature of the data and how they are presented. Because observational studies have limited ability to identify such circumstances, this article argues for an experimental approach that offers greater flexibility in designing theory-based treatments. A vignette experiment methodology approach is used, providing subjects with a variety of budget scenarios, varying the amount and type of information they receive, and asking them to make budget decisions. The results provide evidence that conditions of goal ambiguity, expectancy disconfirmation, and advocacy alter the potential for performance data to influence resource decisions.